Economic indicators for cowpea cultivation under different irrigation depths - Erika de O. T. de Carvalho; Deborah L. P. Costa; Denilson B. da Luz; Matheus L. Rua; Maria de L. A. Velame; Adrielle C. Monteiro; Igor C. de O. Vieira; João V. de N. Pinto; Gabriel S. T. Fernandes; Hildo G. G. C. Nunes; Paulo J. de O. P. de Souza; Marcos A. S. dos Santos (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Cowpeas are of high socioeconomic importance in the North and Northeast regions of Brazil, whereby the search for alternatives that offer increased productivity with financial returns has become an important challenge. Thus, the objective of this study was to estimate and evaluate the economic indicators of cowpea production in 2015 and 2016 when applying drip irrigation to different depths. Irrigation treatments were based on crop evapotranspiration (ETc). The experiment was laid in a randomized complete blocks design with four treatments (0, 25, 50, and 100% ETc) and six replications. For economic analysis, the results were extrapolated to an area of one hectare. Productivity in 2015 was lower than that in 2016; however, in all treatments, it was always higher when plants were grown under adequate water supply. In both years, the total operating costs were higher under irrigation than under rainfed conditions. The 100% ETc treatment resulted in a greater number of cowpea bags (60 kg) produced and a higher gross revenue than the rainfed treatment by 17 bags ha-1, equivalent to 1,020 kg ha-1 (gross revenue US$ 711.48) and 16 bags ha-1, equivalent to 960 kg ha-1 (gross revenue US$ 867.12), in 2015 and 2016, respectively. Water deficit limited cowpea yield in both years but made cultivation economically unfeasible only in 2015.